Efektivitas Media Sosial Instagram untuk Penyebaran Informasi Pajak: Studi Kasus pada Pekerja Generasi Z di Jakarta - Dian Ayu Lestari; Agung Kresnamurti Rivai; Nofriska Krisannya (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to analyze the effectiveness of Instagram social media as a means of disseminating tax information to Generation Z. In the context of the increasing use of social media by this generation of digital natives, the research focuses on five dimensions of effectiveness: participation, openness, conversation, community, and connectedness. The research method used is descriptive quantitative through an online survey using Google Form, which was conducted from November 2024 to February 2025 in the DKI Jakarta area. The sample consisted of 100 Generation Z respondents who actively use Instagram and have accessed tax content. The results showed that the five dimensions of effectiveness obtained an average value above 4.2 (very effective category), with an overall value of 4.29. This shows that Instagram is able to optimally convey tax information to Generation Z, mainly due to its visual and interactive format that suits the characteristics of this generation. In conclusion, Instagram is effective as a tax communication medium, but needs improvement in terms of interactive engagement and connection to official sources. This study suggests that the Directorate General of Taxes continue to develop communicative content, expand digital platforms, and consider a qualitative approach in future research.